Study of the association between postural misalignments in school students - Gouveia, João Pedro (2021)
Nowadays, postural misalignments prevalence in students is increasingly evident and its early detection is the best way to prevent complications in adulthood. It is also known that postural problems appear to have association between them. The aim of this study was to characterize and study the association between spine, scapular and pelvic girdles postural misalignments in 213 school students (124 males and 89 females), aged between 10 and 20 years, from Escola Básica e Secundária de Santa Maria (EBSSM). To understand the relation between postural misalignments we compare the head positioning with the shoulder girdle, the shoulder girdle with the dorsal spine and the lumbar spine with the pelvic girdle. The postural assessment was made by visual scan analysis in a symmetrograph based on photogrammetry and the Adams. We found high percentages of postural misalignments in all subjects. High prevalence was observed in the posterior view of the frontal plane in the head lateral flexion, shoulders vertical asymmetry, scoliosis and in the presence of gibbosity, whereas, in the right view of the sagittal plane forward head posture and protracted shoulders were observed. The lumbar scoliosis was more prevalent in subjects with iliac crest’s asymmetry (p < 0.001) and forward head posture was significantly related to the subjects with protracted shoulders (p = 0.010). The protracted shoulders were more prevalent in subjects with dorsal hyperkyphosis (p = 0.048) and lumbar hyperlordosis was related to the subjects with pelvic anteversion (p < 0.001). The students’ postural assessment showed a wide variety of postural misalignments. It also seems evident that there is a relationship between their occurrences. It should be highlighted the importance of postural assessment in physical education (PE) classes to determine postural misalignments among school students.